Pengaruh Aktivitas Scroll Media Sosial dan Kualitas Interaksi Online Terhadap Kinerja Karyawan: The Effect of Social Media Scrolling Activity and Online Interaction Quality on Employee Performance - Rahmah Aliyyah; Nisrina Khalilah; Hilda Marsida; Alfiyyah Fauziyyah; Salwa Ratu Desyfa; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
The expeditious expansion of social media platforms has fundamentally altered communication dynamics and personal conduct, especially winthin professional environments. The extent of social media engegement, encompassing scrolling habits, content dissemination practices, and the caliber of virtual interactions, is posited to impact employee productivity, whether directly or indirectly. This investigation seeks to assess the repercussions of social media activities and the caliber of online interaction on workforce performance across adult demographics. Employing a quantitative methodology, data were garnered via survey instruments. Followed by the application of statistical techniques to scrutinize interrelations and causal effects among the variables. Findings reveal that the frequency of social media scrolling and content uploading exert a substansial influence on employee performance, whereas the quality of online interactions can either augment or impede individual efficacy. These outcomes imply that social media utilization is contigent not merely on temporal engegement but also on the nature of fostered interactions. Consequently, this research is anticipated to furnish as basis for cultivating digital literacy and strategizing social media management to bolster enhanced employee perfomance.